Formation of cubic Li2TiO3 by mechanical activation and its transformation to monoclinic phase: Stability in helium and hydrogen flows - Carbajal Ramos, Ines Alejandra (2017)
Lithium metatitanate (Li2TiO3) is one of the most attractive candidates as a solid breeder in the blanket of D–T fusion reactors and ionic conductors in lithium-ion batteries. In this work, a new synthesis route, avoiding the use of solvents, high temperatures and dangerous sub-products, is used to obtain cubic and monoclinic Li2TiO3 nanopowders. This method consists of ball milling of LiCl, TiO2 and NaOH in air atmosphere at room temperature and posterior calcination. Structural, microstructural and textural characteristics of the Li2TiO3 powders as well as of the pellets before and after annealing were determined. Remarkable contraction of the material and high mechanical stability was observed after treatment at 800 °C for 5 h. Finally, the behaviour in reductive and inert atmospheres of the sintered and green pellets was studied, characterizing the extension and impact of the reactions on the physicochemical and structural stability of the material. It can be concluded that the sintered pellets became mechanically stable due to the thermal treatment, showing no physicochemical modifications after analysis in different atmospheres up to 800 °C.